PENGARUH STRATEGI PEMASARAN TERHADAP FUNDING DAN LENDING DI BMT AT-TAJDID TEMAYANG BOJONEGORO - Nur Musfia; Arivatu Ni’mati Rahmatika; Ashlihah - (DINAMIKA : Jurnal Kajian Pendidikan dan Keislaman, 2020)
Baitul Mal Wat Tamwil is a sharia-based financial institution that manages the financial deposits and financing. Strategy in Marketing BMT At-Tajdid Temayang Bojonegoro Temayang planned to build community confidence that BMT At-Tajdid Temayang Bojonegoro is a business hall in which there are activities to develop Productive efforts and investments in improving the quality of economic activity and also building community confidence that at the BMT At-Tajdid Temayang Bojonegoro can manage the savings with the trust, but with the marketing strategy Whether BMT as a financial institution can compete with conventional financial institutions although the products, prices, places, and promotions have not been adequate so that the main problem will be observed by researchers. The results showed that the variable marketing strategy (product, price, place, promotion) simultaneously had an effect on funding and lending. It can be proved that the value F count > F table or 99.847 > 4.20. While based on a partial test of a variable marketing strategy the product has a significant effect on funding and lending, it can be proved that the product marketing strategy value T count more > T table or 3.709 > 2.059, price 0.045 > 0.50, place 0.240 > 0.50, Promotion 2.205 > 2.059. The results of this test resulted in a coesophageal determination (R ²) of 0.963 That means 96.3% of the marketing strategy variable in the influence of variable funding and lending while the remaining 3.7% in the influence of other variables that are not conscientious in research This.